PENGEMBANGAN MEDIA PEMBELAJARAN SMARTBOARD PADA KETERAMPILAN MENULIS TEKS NARASI SISWA KELAS V SD NEGERI 09 KOTO BARU - Dodi Widia Nanda; Amar Salahuddin; Rizki Fajri Jumaris (STKIP Subang, 2024)
This research was motivated by the lack of teaching materials in the learning process, especially in making teaching materials. The teaching materials used in this school still use textbooks and worksheets as the teaching materials used. The school needs creative teaching materials that can attract students' attention in the learning process, while students like to learn using interesting learning media, in this school there is a lack of interesting learning media. In this research, researchers want to develop smartphone learning media. This research aims to develop smartphone learning media that is made attractive and creative. Types of research and development Research and Development (R&D). The model used in this research is the 4-D model consisting of 4 stages, namely the definition stage (Define), the design stage (Design), the development stage (Develop), the deployment stage (Dessiminate). The types of data collection taken in this research were interview sheets, validity, practicality and effectiveness instruments. Data collection techniques use observation, interviews, questionnaires and documentation techniques. Data analysis techniques include validity, practicality and effectiveness data analysis. The validation results by graphics experts were 70.4% in the very valid category, content/material experts 83.3% in the valid category, linguists 89.2% in the very valid category. the results of the questionnaire data analysis, the responses of teachers and class IV students were 100% in the very practical category. The results of effectiveness data analysis through test questions with an average score of 87.5% in the effective category.